Dampak Galian C Terhadap Lingkungan Alam Masyarakat Lingkar Tambang di Kota Ternate - Rosita Rosita; Karmila Ibrahim; Gunawan Gunawan (Universitas Khairun, 2022)
The mining activity of post-excavation soil C in Kalumata, Ternate, North Maluku had impact on the environment and the socio-economic of the local community. This study conducted to determine the environmental impact of the post-excavation soil C mining activity in Kalumata, Ternate on the local community. Physical and chemical data were taken at 3 distances, namely 17 meters, 300 meters, and 800 meters. The results showed that the farther the distance, the lower the pH of the soil. The lowest soil pH was detected at a distance of 800 meters. Soil texture in the form of sand composition decreased and the clay content became high. The highest soil moisture was at the distance of 300 and 800 meters (71%). The highest wind speed was at the distance of 300 meters (75.1 km/hour). The result of CO, TVOC and HCHO analysis using CO at a distance of 17 meters, 300 meters and 800 meters were 0.993 ppm, 0.563 ppm, and 0.579 ppm. This values were still in the good category.Keywords: post-excavation soil C, mining line, air quality standards